2020
DOI: 10.3390/ijerph17249567
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Electrical Activity of the Brain in the Alpha and Theta Bands during Prayer and Meditation

Abstract: Focused attention meditation (FAM) is a category of meditation based on an EEG pattern, which helps the wandering mind to focus on a particular object. It seems that prayer may, in certain respects, be similar to FAM. It is believed that emotional experience correlates mainly with theta, but also with selective alpha, with internalized attention correlating mainly with the synchronous activity of theta and alpha. The vast majority of studies indicate a possible impact of transcendence in meditation on the alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…With meditation, a slowing of brain activity is observed with decreased hemispheric asymmetry. Prior research has found that effective meditation led to slowed down synchronous alpha activity with an overall shift towards the parasympathetic system [50]. The stress segment in this study increased both the beta and alpha band powers as expected, with an increase in hemispheric asymmetry.…”
Section: Resultssupporting
confidence: 81%
“…With meditation, a slowing of brain activity is observed with decreased hemispheric asymmetry. Prior research has found that effective meditation led to slowed down synchronous alpha activity with an overall shift towards the parasympathetic system [50]. The stress segment in this study increased both the beta and alpha band powers as expected, with an increase in hemispheric asymmetry.…”
Section: Resultssupporting
confidence: 81%
“…By aversive, we refer to emotional states experienced as aversive, while pleasant refers to the opposite. In other words, meditation can reduce aversive feelings by developing mental habits that reduce this amplification and catastrophizing process, and this in itself may be one of the most important beneficial mechanisms through which FAM relieves mood and stress [14,15].…”
Section: Focused-attention Meditationmentioning
confidence: 99%
“…In summary, communication, work stress, and job satisfaction are important factors influencing safety attitudes [44]. FAM can help relieve stress, regulate mood, and reduce work stress [14,15]. Improved concentration makes surgeons more focused on the work at hand, less likely to be distracted, more likely to enter the state of flow, experience pleasure, and, thus, improve job satisfaction.…”
Section: Patient Safety and Safety Attitudementioning
confidence: 99%
“…La integración entre los dos mundos, ya perfilada desde la presentación del caso de Leborgne, fue adquiriendo forma y nutriéndose de una constelación de evidencias provenientes principalmente de la neuroimagenología, traspasando las fronteras del lenguaje y llegando a terrenos como el de la adopción de decisiones (Camerer & Mobbs, 2017; Ramakrishnan & Murthy, 2013), los estilos cognoscitivos (Hao, et al, 2014;Miller, et al, 2012), la ejecución de tareas mentales (Nishimura, et al, 2020), sentimientos como el amor (Zeki, 2007), el odio (Zeki & Romaya, 2008) o el remordimiento (Duan, et al, 2020;Takahashi, et al, 2004), aspectos como la religiosidad o espiritualidad (Dobrakowski, et al, 2020;Bouso, et al, 2015), la empatía (Weisz & Zaki, 2018;Bernhardt & Singer, 2012), la imaginación (Fulford, et al, 2018), la ética y la moral (Eslinger, et al, 2009;Moll, et al, 2002), y la autoconsciencia (Lou, et al, 2017;Hameroff, 2001).…”
Section: Consciencia Y Cogniciónunclassified